Excitation energy transfer in europium complexes with doxycycline in the presence of surfactant micelles and silver nanoparticles - Danilina, Tatiana Grigorievna; Syardina, Alina V.; Timonova,, Ekaterina R.; Nevryueva, Natalia Vladimirovna; Smirnova, Tatiana D. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
Doxycycline is a broad-spectrum tetracycline antibiotic used to treat infections in humans and in veterinary medicine as a prophylactic drug and growth stimulant. For this reason, residual amounts of antibiotics in milk, meat and other food products can cause resistance and the development of allergies. In this regard, constant monitoring of residual contents of tetracyclines in food products, environmental objects, and biological fl uids is required. The purpose of this work was to study the eff ect of spherical silver nanoparticles and surfactant micelles on the intensity of sensitized fl uorescence of europium ion complexes with doxycycline and to develop a new sensitive and simple method for the fl uorimetric determination of doxycycline in solutions. As a result of the simultaneous infl uence of the energy of an external excitation source and the surface plasmon resonance of silver nanoparticles on doxycycline, the intensity of its fl uorescence increases. The probability of the ligand transition to the excited state increases signifi cantly, which contributes to the most effi cient implementation of intramolecular excitation energy transfer in the Eu3+ complex with doxycycline. We have shown that in the presence of silver nanoparticles and Eu3+ ions, the fl uorescence intensity of an analytical system containing doxycycline increases 125 times. In the presence of the nonionic surfactant Tween-80, the sensitized fl uorescence signal of the Eu3+ chelate with doxycycline increases by more than 19 times. Solubilization of the components of the analytical reaction into micelles of surfactants helps to change their protolytic properties, dehydration, increase the stability of the complexes, and the effi ciency of intramolecular energy transfer. In the combined presence of Tween-80 surfactant micelles and silver nanoparticles, an additional 27-fold increase in the fl uorescence intensity of the metal ion chelate with doxycycline is observed. Based on the conducted research, a method for the fl uorimetric determination of doxycycline using Tween-80 micelles, silver nanoclusters and Eu3+ ions in natural water has been proposed. The range of detectable concentrations is 1.0·10-7–1.0·10-5 M, detection limit (Limit of Detection) 6.0·10-8М (3 σ). The correctness of the defi nition has been controlled by the “entered–found” method.